Violence against women and children in conflict zones: legal protection - Hamid, Abdul Ghafur@Khin Maung Sein (2017)
Enforcement is extremely difficult on account of the collapse of system of justice and the rule of law in conflict zones. It is imperative, therefore, that after the conflict, the rule of law should be promptly restored in the process of ‘peace-building,’ and all the perpetrators during the conflict should be held accountable. National courts should be given the first priority for prosecution and ICC should step in only when necessary. The UN Security Council should exercise Chapter VII enforcement powers to address serious and widespread cases of violence against women and children in conflict situations, by deciding that it is a threat to international peace and security.